Simulación numérica del comportamiento de las corrientes de aire para el aprovechamiento de aire en la Universidad de América. (2023)
This article shows the analysis of air currents for the University of America using numerical simulations of computational fluid dynamic which have an important role in providing efficiently and accurately results corresponding to the air flow in relation to speed. The behavior of air currents is evaluated using certain parameters and flow conditions, such as temperature, speed, density and geometric characteristics. This document shows the development of a simulation with an air current flow determined by the south and west direction, the data was provided by the Institute of Hydrology, Meteorology and Environmental Studies (Ideam), and were use in a computational model of the geometry of the infrastructure of the university, where different parameters related to the discretization of the domain, the initial conditions and the border conditions were applied, the results of this analysis show an average air speed between 12.45 m/s and 17.79 m/s, from where It is concluded that the implementation of wind energy in the university is feasible.